Sistem Saraf Pusat dan Perifer - Syalwa Meutia Syalwa Meutia; nurul utami; Rani Himayani; selvi rahmawati (Medula, 2021)
The structure of the central nervous system consists of the cerebrum, cerebellum, and spinal cord which are located in the cranial cavity and vertebral canal. The primary functional unit of the neural network is nerve cells (neurons) which function to form and transmit information in the form of electrical impulses and supporting cells (neuroglia) which are located around neurons and are more numerous than neurons. The parts of a neuron include the cell body (soma or perikaryon), dendrites and axons. Based on the number of dendrites and axons, neurons are classified into multipolar, bipolar and pseudounipolar neurons. Neuroglia consist of astrocytes, oligodendrocytes, microglia, and ependymal cells. Neuroglia play a role in providing a conducive microenvironment for the activity of neurons. The peripheral nervous system is a nervous system that connects all parts of the body with the central nervous system, this system consists of nervous tissue located outside the brain and spinal cord (spinal cord) such as the skin and other senses, the peripheral nervous system consists of cells Nerve cells group together to form ganglia, nerve fibers, and nerve end bodies